2010
DOI: 10.1002/micr.20726
|View full text |Cite
|
Sign up to set email alerts
|

Total obstetric brachial plexus palsy: Results and strategy of microsurgical reconstruction

Abstract: From 2000 to 2006, 35 infants with total obstetric brachial plexus palsy underwent brachial plexus exploration and reconstruction. The mean age at surgery was 10.8 months (range 3-60 months), and the median age was 8 months. All infants were followed for at least 2.5 years (range 2.5-7.3 years) with an average follow-up of 4.2 years. Assessment was performed using the Toronto Active Movement scale. Surgical procedures included neurolysis, neuroma excision and interposition nerve grafting and neurotization, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
0
22
1
Order By: Relevance
“…When statistically analyzed, our results for group 1 and 2 seem similar, with the exception of shoulder abduction, but not statistically significantly. The results of global shoulder recovery and elbow flexion in the present study and also in a number of published series are good [3,9,13,21,32]. In contrast, the results with regard to external rotation were poor; successful results were achieved in 50 % in group 1 and 25 % in group 2.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…When statistically analyzed, our results for group 1 and 2 seem similar, with the exception of shoulder abduction, but not statistically significantly. The results of global shoulder recovery and elbow flexion in the present study and also in a number of published series are good [3,9,13,21,32]. In contrast, the results with regard to external rotation were poor; successful results were achieved in 50 % in group 1 and 25 % in group 2.…”
Section: Discussioncontrasting
confidence: 62%
“…Pondag et al, in a series of 86 patients, found that only 20 % achieved more than 20 degrees of true glenohumeral external rotation [23]. El-Gammal et al found 34 % and 54 % after tendon transfers [9]. No difference in final external rotation was found between patients who underwent nerve grafting from the proximal stump of C5 and patients who underwent spinal accessory nerve transfer [23,30].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nerve grafting can result in improved motor function and sensibility. Although difficult to compare due to variable indications and scoring systems, studies have consistently demonstrated significant functional gains in elbow flexion in patients who undergo surgery between 3 and 9 months [14,51,52]. Nerve transfers have gained popularity over the past decade.…”
Section: Microsurgical Techniquesmentioning
confidence: 99%
“…Many studies that were published by other Egyptian centers 2,5,6 showed the incidence and management of those cases, however, in this study we focus only on the traumatic type of the BPI. This study has been designed to evaluate the epidemiological, clinical, and outcome of traumatic brachial plexus injuries in our institutions.…”
Section: Introductionmentioning
confidence: 99%